2018
DOI: 10.1186/s12866-018-1353-y
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Coxiella burnetii in sheep and goat abortion samples

Abstract: BackgroundQ fever, caused by Coxiella burnetii, is a zoonosis that presents a worldwide distribution and affects both humans and animals. The route of dispersal of the pathogen by ruminants into the environment usually involves stages of abortion and parturition, nevertheless the agent can, also, be detected in other animal samples. Therefore it is considered as important in terms of proper diagnosis, as well as, for epidemiology and surveillance purposes, to genotype the pathogen. The aim of the current study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Although validated commercial ELISA kits are routinely used for the detection of C. burnetii in productive animals with high sensitivity and specificity, a limitation of our study is that we did not confirm our results by a specific immunofluorescence assay (IFA). Moreover, we did not perform molecular assays in positive samples to detect the C. burnetii genotypes that circulate in productive animals in Greece (Chochlakis et al., 2018). We believe that the determination of C. burnetii genotypes would be important as the clinical manifestations of Q fever in human depend, at least in part, on the C. burnetii genotype (Angelakis et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although validated commercial ELISA kits are routinely used for the detection of C. burnetii in productive animals with high sensitivity and specificity, a limitation of our study is that we did not confirm our results by a specific immunofluorescence assay (IFA). Moreover, we did not perform molecular assays in positive samples to detect the C. burnetii genotypes that circulate in productive animals in Greece (Chochlakis et al., 2018). We believe that the determination of C. burnetii genotypes would be important as the clinical manifestations of Q fever in human depend, at least in part, on the C. burnetii genotype (Angelakis et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, we recently raised the question of the under-diagnosis of human C. burnetii infections in Greece (Karageorgou et al, 2020). Previously, it was found that the C. burnetii genotype MST32 is circulating in sheep and goat at eight different areas of Northern Greece (Chochlakis et al, 2018). However, most…”
Section: Burnetii Could Also Cause Obstetric Complications Includimentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we identified a new C. burnetii genotype in the aortic valve of a patient who had Q fever endocarditis. Recently, it was found that C. burnetii genotype 32 is circulating in sheep and goat in 8 different areas of Greece (10). The clinical manifestations of Q fever depend, at least in part, on the C. burnetii genotype (5).…”
Section: Research Lettersmentioning
confidence: 99%
“…MST genotyping reveals that the spacer types (ST)-8, ST-18, ST-20 are widespread over Europe, while other genotypes were found only in some countries (i.e. ST-32 in Greece and central Italy, ST-13 in Spain and Portugal, ST-4 in France and Portugal, ST-17 in French Guiana) (Glazunova et al, 2005;Chmielewski et al, 2009;Astobiza et al, 2012;Reichel et al, 2012;Santos et al, 2012;Di Domenico et al, 2014;Sulyok et al, 2014;Ceglie et al, 2015;Chochlakis et al, 2018).…”
mentioning
confidence: 99%